2003
DOI: 10.1111/j.1572-0241.2003.07497.x
|View full text |Cite
|
Sign up to set email alerts
|

Portal Pressure Response To Losartan Compared With Propranolol in Patients With Cirrhosis

Abstract: Losartan is as effective as propranolol in reducing portal pressure in cirrhotic patients who are not receiving diuretics. Losartan is also superior to propranolol for achieving target level hepatic venous gradient for prevention of variceal bleeding in nonascitic and alcohol-abusing cirrhotic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 31 publications
2
36
0
1
Order By: Relevance
“…For example, fibrosis in liver, kidney, lung, and heart have been linked to AngII activity in experimental animal models. [3][4][5] In humans, it has been shown that losartan, an angiotensin II type 1 (AT1) receptor antagonist, not only decreases portal pressure in cirrhosis, 6 but also may have antifibrotic effects in liver. 7 Therefore, the RAS seems to play key roles in tissue remodeling and scarring, especially after injury.…”
mentioning
confidence: 99%
“…For example, fibrosis in liver, kidney, lung, and heart have been linked to AngII activity in experimental animal models. [3][4][5] In humans, it has been shown that losartan, an angiotensin II type 1 (AT1) receptor antagonist, not only decreases portal pressure in cirrhosis, 6 but also may have antifibrotic effects in liver. 7 Therefore, the RAS seems to play key roles in tissue remodeling and scarring, especially after injury.…”
mentioning
confidence: 99%
“…In addition, Lay et al 18 documented that 16% of patients had to withdraw from the propranolol therapy due to adverse events such as hypotension and dizziness. However, in other literatures, 6,10 no adverse effects were observed throughout the study. In the present study, the only complication noted was dizziness: this was found in 24% of the patients treated with propranolol.…”
Section: Discussionmentioning
confidence: 61%
“…Von Bergmann et al reported that after once-daily oral doses of 10 mg olmesartan were given to patients with mild and moderate hepatic impairment (Child-Pugh scores of B6 and 7-9, respectively), the daily maximum concentration of the drug in the body was generally similar to that in healthy matched subjects, but the area under the curve increased by 30 and 48%, respectively, and was reflected in increases of absolute bioavailability values compared with those in healthy subjects [23]. De et al [24] showed that low-dose losartan was as effective as propranolol in reducing portal pressure in cirrhotic patients. On the other hand, Schepke et al [25] showed that another ARB, irbesartan, moderately reduced portal pressure but induced marked arterial hypotension and renal impairment in patients with advanced cirrhosis.…”
Section: Discussionmentioning
confidence: 96%